Characterization of irradiated mucosa using confocal laser endomicroscopy in the upper aerodigestive tract - Thesing, Lisa; Sievert, Matti; Panuganti, Bharat Akhanda; Aubreville, Marc; Meyer, Till; Müller-Diesing, Flurin; Scherzad, Agmal; Hackenberg, Stephan; Goncalves, Miguel (European Archives of Oto-Rhino-Laryngology, 2025)
Purpose: Confocal laser endomicroscopy (CLE) enables a real time in-vivo optical biopsy of the upper aerodigestive tract. Previous studies demonstrated its potential in identifying malignant tissue, but none examined mucosa treated with radiotherapy. This study characterizes the appearance of irradiated mucosa using CLE. Methods: We recorded 58 CLE sequences (860 s, 6,884 frames) in 10 patients previously treated with radiotherapy for upper aerodigestive tract tumors. A corresponding tissue biopsy (formalin-fixed, H&E stained) was taken as the reference standard for each sequence. We analyzed each sequence regarding differences from normal mucosa and characterized irradiated mucosa in CLE. Results: Irradiated mucosa in CLE exhibits irregular tissue architecture. Radiation induces DNA damage, apoptosis, and tissue inflammation, leading to hyperkeratotic and fibrotic tissue. Consequently, CLE showed a wider range of cellular morphologic and tissue structural aberrancies, in comparison to normal, non-irradiated mucosa. In addition to regular honeycomb-like patterns, the tissue displayed uneven, blurry, and cell-rich areas. Irradiated mucosa appears more irregular and variable in CLE than radiation-naïve mucosa. Conclusion: Irradiated mucosa can be differentiated from healthy tissue using CLE, but its higher baseline morphological variability may mimic malignancy. Further research is needed to clarify its impact on tumor detection and refine existing scoring systems.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Confocal laser endomicroscopy; Diagnostic; Head and neck cancer; Irradiated mucosa; Radiotherapy